Bouguer Density Analysis using Nettleton Method at Banten NPP Site - Yuliastuti Yuliastuti; Hadi Suntoko; Yarianto Sugeng Budi Susilo (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2017)
BOUGUER DENSITY ANALYSIS USING NETTLETON METHOD AT BANTEN NPP SITE. Sub-surface information become crucial in determining a feasible NPP site that safe from external hazards. Gravity survey which result as density information, is essential to understand the sub-surface structure. Nevertheless, overcorrected or under corrected will lead to a false interpretation. Therefore, density correction in term of near-surface average density or Bouguer density is necessary to be calculated. The objective of this paper is to estimate and analyze Bouguer density using Nettleton method at Banten NPP Site. Methodology used in this paper is Nettleton method that applied in three different slices (A-B, A-C and A-D) with density assumption range between 1700 and 3300 kg/m3. Nettleton method is based on minimum correlation between gravity anomaly and topography to determine density correction. The result shows that slice A-B which covers rough topography difference, Nettleton method failed. While using the other two slices, Nettleton method yield with a different density value, 2700 kg/m3 for A-C and 2300 kg/m3 for A-D. A-C provides the lowest correlation value which represents the Upper Banten tuff and Gede Mt. volcanic rocks in accordance with Quartenary rocks exist in the studied area.